Clinical and epidemiological characteristics of respiratory syncytial virus, SARS-CoV-2 and influenza paediatric viral respiratory infections in southwest Saudi Arabia - Ali Alsuheel Asseri; Saleh M. Al-Qahtani; Ibrahim A. Alzaydani; Ahmed Al-Jarie; Noha Saad Alyazidi; Ali A. Alrmelawi; Alya Musfer Alqahtani; Rahaf S. Alsulayyim; Ameerah K. Alzailaie; Dhay M. Abdullah; Abdelwahid S. Ali (Annals of Medicine)
Background There is a global consensus that respiratory tract infections are the major causes of morbidity and mortality among children. In this study, we aimed to compare the clinical and epidemiological characteristics of respiratory syncytial virus (RSV), influenza and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections among children admitted to hospital with acute respiratory infections. We also opted to identify the predictors of paediatric intensive care unit (PICU) admission.Methods In this study, a retrospective investigation and analysis of 423 children who were admitted to Abha Maternity and Children Hospital, in the southern region of Saudi Arabia, between January and December 2022 were conducted.Results The median age of these children was 16.5 months (Q1–Q3: 6–46.3). It was observed that the infectivity levels of RSV, SARS-CoV-2, influenza A and influenza B infections peaked in early to mid-September, mid-July, May and June, and October, respectively. There was a statistically significant difference in the total WBC counts between RSV and influenza B (p = 0.035) and SARS-CoV-2 and influenza B (p = 0.013). Moreover, there was a statistically significant difference in the absolute lymphocyte count between influenza A and RSV (p = 0.002). The median number of days in hospital was 6 days (Q1–Q3: 4–10). Patients with RSV infection required a significantly longer hospital stay, with a median of 8 days (Q1–Q3: 4–10). The factors associated with the likelihood of PICU admission for all study participants were congenital heart disease (odds ratio (OR) = 2.9, 95% confidence intervals (CI) [1.4–6.1]), RSV (OR = 2.3, 95% CI [1.3–4.1]) and age <6 months (OR = 2.0, 95% CI [1.2–3.4]).Conclusions RSV was identified as the most common pathogen causing acute lower respiratory infections among the studied patients. One of the more significant findings to emerge from this study is the seasonal changes in RSV and influenza infections, which mandates further research.